2014
DOI: 10.1111/obr.12162
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and body weight status: a systematic review and meta‐analysis of randomized controlled trials

Abstract: Vitamin D is anticipated to have many extra-skeletal health benefits. We questioned whether supplementation with the vitamin influenced body weight and composition. A systematic review and meta-analysis was conducted on high-quality, randomized controlled trials (RCTs) that had supplemented vitamin D without imposing any caloric restriction. Eighteen trials reporting either body weight, body mass index (BMI), fat mass (FM), percentage fat mass (%FM) or lean body mass (LBM) met our criteria. Twelve studies prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 52 publications
(57 reference statements)
1
56
0
1
Order By: Relevance
“…8 Although these results consistently suggest that higher 25(OH)D levels may be associated with less body fat accumulation in older women, results from a meta-analysis of 12 clinical trials (some including older adults) indicate that vitamin D supplementation without caloric restriction does not significantly influence fat mass. 13 Our study is limited by the short follow-up time, the medium sample size, a missing assessment of weight history and the small total change in weight and body fat. Bioelectrical impedance analysis was found to be valid to track changes in fat mass in older adults, but it might not accurately estimate changes of o5 kg.…”
Section: Discussionmentioning
confidence: 97%
“…8 Although these results consistently suggest that higher 25(OH)D levels may be associated with less body fat accumulation in older women, results from a meta-analysis of 12 clinical trials (some including older adults) indicate that vitamin D supplementation without caloric restriction does not significantly influence fat mass. 13 Our study is limited by the short follow-up time, the medium sample size, a missing assessment of weight history and the small total change in weight and body fat. Bioelectrical impedance analysis was found to be valid to track changes in fat mass in older adults, but it might not accurately estimate changes of o5 kg.…”
Section: Discussionmentioning
confidence: 97%
“…[13][14][15] In several studies, VFA showed significant correlation with blood vitamin D levels, although weight, waist circumference but not BMI. 16,17) As not improve obesity-related variables, 23,24) whereas other meta-analysis presented that blood vitamin D levels increase as weight or PBF decreases. 25) Sun et al 16) demonstrated that serum vitamin D levels are negatively correlated with VFA using magnetic resonance imaging (MRI), which is in correspond with outcome of our study, But not BMI.…”
Section: Relation Analysis Of Vitamin D and Obesity-related Variablesmentioning
confidence: 94%
“…Although vitamin D is not present naturally in most foods, it is commonly added into some manufactured foods, as fruit juices and fruit juice drinks, beverages, cheese and cheese products [19,20]. Value of Vitamin D in foods is reduced by cooking, such as by boiling, frying or baking.…”
Section: Dietary Sources Of Vitamin Dmentioning
confidence: 99%